2019
DOI: 10.1002/slct.201902646
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of NaYF4:Yb,Tm@TiO2 Core‐Shell Structured Composite with Enhanced Photocatalytic Activity for Degradation of RhB Dye

Abstract: It is an effective method to explore the full spectrum responsive photocatalysts for enhancing their photocatalytic activity. Herein, we have combined the upconversion phosphor with semiconductor to design the full‐spectrum light responsive photocatalyst. A facile approach has been developed for synthesis of NaYF4:Yb,Tm@TiO2 core‐shell structured composite. The morphologies, crystal phases, chemical compositions, optical performance, and photoelectric properties were characterized. Based on SEM and TEM observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The Yb,Tm doped β-NaYF 4 phase is shown to be the most appropriate choice for that, since Tm 3+ ions UV emission matches well with the absorption band of TiO 2 [11]. Mostly, studies have shown that NaYF 4 Yb,Tm@TiO 2 enables efficient degradation of dyes under NIR light [12][13][14][15]. There are only a few reports on sunlight-driven photocatalytic efficiency toward the degradation of other pollutants, such as microcystin [11] and ciprofloxacin [16].…”
Section: Introductionmentioning
confidence: 99%
“…The Yb,Tm doped β-NaYF 4 phase is shown to be the most appropriate choice for that, since Tm 3+ ions UV emission matches well with the absorption band of TiO 2 [11]. Mostly, studies have shown that NaYF 4 Yb,Tm@TiO 2 enables efficient degradation of dyes under NIR light [12][13][14][15]. There are only a few reports on sunlight-driven photocatalytic efficiency toward the degradation of other pollutants, such as microcystin [11] and ciprofloxacin [16].…”
Section: Introductionmentioning
confidence: 99%